Efficacy of electroconvulsive therapy in Parkinson's disease: A clinical trial. (16th February 2022) - Afshari, Daryoush; Shakeri, Jalal; Khodamoradi, Mehdi; Abadi, Reza Nejad Shahrokh; Rahkan, Jaza; Afshar Hezarkhani, Leila
Highlights: ECT could effectively relieve the relevant motor and psychiatric symptoms in PD patients. ECT should be performed at regular intervals in order to maintain their effects as its effectiveness waned over time. Abstract: Motor and psychiatric symptoms in patients with Parkinson's disease (PD) constitute some of the most problematic issues for both the patients and their caregivers. This study evaluated the short- and long-term efficacy of electroconvulsive therapy (ECT) in PD patients whose psychiatric symptoms had been exacerbated due to drug therapy. Fifteen PD patients were treated using an electroshock device at a range of 25–100 Joules over a period of 6 weeks, during 12 sessions. Motor and psychiatric symptoms of all patients were evaluated before conducting ECT as baseline, after 12 sessions of ECT at the 6th week, and one month after completion of the treatment at the 10th week. The results showed that the variables mentation, behavior, mood, performance of daily activities, and severity of motor and psychiatric symptoms, were significantly improved at the end of the 6th and 10th weeks when compared with the baseline. Moreover, the results revealed that the mean values were significantly different only for motor symptoms at the end of the study (10th week) compared with the second time point. The current trial may indicate that ECT could potentially serve as a viable treatment for PD patients with refractory psychiatric symptoms. However, due to waning efficacy of ECT, it is recommended that PD patients undergo a conventional treatment in conjunction with periodic ECT sessions to ensure an optimal medical outcome.